3D Propolis-Sodium Alginate Scaffolds: Influence on Structural Parameters, Release Mechanisms, Cell Cytotoxicity and Antibacterial Activity - AKSU, MEHMET BURAK; UZUN, MUHAMMET; GÜNDÜZ, OĞUZHAN (MDPI, 2020)
In this study, the main aim was to fabricate propolis (Ps)-containing wound dressing patches using 3D printing technology. Different combinations and structures of propolis (Ps)-incorporated sodium alginate (SA) scaffolds were developed. The morphological studies showed that the porosity of developed scaffolds was optimized when 20% (v/v) of Ps was added to the solution. The pore sizes decreased by increasing Ps concentration up to a certain level due to its adhesive properties. The mechanical, swelling-degradation (weight loss) behaviors, and Ps release kinetics were highlighted for the scaffold stability. An antimicrobial assay was employed to test and screen antimicrobial behavior of Ps against Escherichia coli and Staphylococcus aureus strains. The results show that the Ps-added scaffolds have an excellent antibacterial activity because of Ps compounds. An in vitro cytotoxicity test was also applied on the scaffold by using the extract method on the human dermal fibroblasts (HFFF2) cell line. The 3D-printed SA-Ps scaffolds are very useful structures for wound dressing applications.
Keywords: 3D printing; propolis; sodium alginate; tissue scaffold; wound treatment; BRAZILIAN RED PROPOLIS; IN-VITRO; BIOLOGICAL-PROPERTIES; CHEMICAL-COMPOSITION; ANTIVIRAL ACTIVITY; DRESSINGS; FILMS; ANTIOXIDANT; EXTRACTS; DEGRADATION